Terracene : a crude aesthetics - Mameni, Salar, 1977- (ANIMA (Duke University Press), 2023)
"In Terracene, Salar Mameni shows how the racialized construction of terror in the Western political imagination and critical discourse concerning the threat of anthropogenic climate change have developed in conjunction with one another. Through the logic of the Anthropocene, ecological catastrophe has become enclosed within state discourse on terror, and natural disasters, viruses, pollution and other "non-human" dangers have been conflated with the threat of political violence by the "less-than-human" racialized other. Terracene challenges this false equivalence by examining how West Asian artists and knowledge producers confront the "weaponized ecologies" of their homelands and discover ways of living with what Mameni calls terrans-"the mountains, wetlands, viruses, smoke plumes, mutated cells and crude oil" that make up our world"--